Food insecurity, leadership, and organizational performance: A case study in the Diocese of Soacha - Villamizar Moreno, Henry Armando (2024)
The research analyzes the influence of leadership styles in the “Tejiendo Comunidad” program of the Episcopal Vicariate for Social Care in the Diocese of Soacha, Colombia. The paper evaluates how leadership styles affect the performance of the program that addresses food insecurity in the vulnerable population where the Diocese has a presence through 46 parishes, 1 quasi-parish2, and 3 chapels, providing nearly 3,700 food packages per month. In this research, a correlational and inductive approach was applied with three instruments: a survey of 462 families, the Blake and Mouton test to identify leadership styles, and the Organizational Performance Index (OPI) applied to 14 leaders. Results emphasize that leadership styles do not affect program results. Leaders’ gender and age are not variables that affect the results of a program applied to a population with four ethnic groups characterized as being in a vulnerable situation.